Carbonized Wood Decorated with Cobalt‐Nickel Binary Nanoparticles as a Low‐Cost and Efficient Electrode for Water Splitting. (7th May 2021) - Gan, Wentao; Wu, Lianping; Wang, Yaoxing; Gao, He; Gao, Likun; Xiao, Shaoliang; Liu, Jiuqing; Xie, Yanjun; Li, Teng; Li, Jian
Abstract: Using an inexpensive and eco‐friendly wood substrate, herein, a one‐step calcination method is developed to deposit Co‐Ni binary nanoparticles into aligned wood channels and an effective carbonized wood (CW) electrode (termed as Co/Ni‐CW) is fabricated. Well distributed Co‐Ni nanoparticles are achieved by the coordination bonds between the hydroxyl groups on wood matrix and soaked metal cations. Subsequently, high‐temperature calcination promotes the nucleation of Co‐Ni nanoparticles and the formation of CW. With the uniform distribution of Co‐Ni nanoparticles and porous wood structure, not only is a high active surface area, but also the electron and mass diffusion pathways are enhanced. Thus, the as‐prepared Co/Ni‐CW affords the current density of 10 mA cm –2 at low overpotentials of 330 and 157 mV for oxygen and hydrogen evolution, respectively. Remarkably, when the wood‐based bifunctional electrocatalyst is used as both the anode and cathode, a low cell voltage of 1.64 V is required to reach the current density of 10 mA cm –2 . Compared with most substrates used in bifunctional electrocatalysts, the abundance, low cost, eco‐friendliness, and easy operation of wood‐based catalysts allow for an active and scalable electrode for water splitting and many other energy storage devices. Abstract : A one‐step calcination strategy is demonstrated to deposit Co‐Ni binary nanoparticles into aligned wood channels and fabricate an effective and low‐cost carbonized wood electrode. The carbonized wood electrode demonstrates both enhanced oxygen evolution reaction and hydrogen evolution reaction performances, holding great potential for overall water splitting.